Effect of Mesenchymal Stem Cells and Platelet-Rich Plasma on the Bone Healing of Ovariectomized Rats - Bo Wei; Chengshuo Huang; Mingyan Zhao; Peng Li; Xiang Gao; Junchao Kong; Yanru Niu; Rui Huang; Juanhua Quan; Jinsong Wei; Jiaqi Chu (Hindawi Limited, 2016)
We evaluated the efficacy of platelet-rich plasma (PRP) in combination with allogeneic bone marrow mesenchymal stem cells (BMSCs) for the treatment of osteoporotic bone defects in an ovariectomized rat model. By day 42 after injury, in vivo microcomputed tomography (micro-CT) imaging revealed that bone defects of control rats and ovariectomized rats treated with PRP and BMSCs were completely repaired, whereas those of ovariectomized rats treated with PRP or BMSCs alone exhibited slower healing. Histological data were consistent with these results. We also assessed changes to bone trabeculae in the proximal tibial growth plate. In ovariectomized rats treated with PRP or with a combination of PRP and BMSCs, the trabecular connectivity densities (Conn.D), bone volume ratios (BV/TV), and numbers (Tb.N) in the defect areas increased significantly from day 7 to day 42. These results indicate that PRP treatment enhances bone microarchitecture in osteoporosis. Moreover, expression levels of osteogenesis-specific marker genes including RUNX2, OSX, and OPN were significantly upregulated in rats treated with PRP and BMSCs compared to those of other groups. Thus, we conclude that treatment with PRP combined with BMSCs significantly promotes healing of osteoporotic bone defects. This study provides an alternative strategy for the treatment of osteoporotic bone loss.